(untitled) (Architecture Image Studies, 2025)
Businesses that are run by family companies, supervision and planning are very important to achieve productivity so that the company always gets the expected profit, so family companies need to build competitiveness and marketing strategies. This study aims to analyze the effect of competitiveness and marketing strategy on business productivity, analyze the effect of competitiveness, marketing strategy, and business productivity on profit, and analyze the effect of business productivity mediating the effect of competitiveness and marketing strategy on family business profits. The population in this study were the heads of family companies from 220 companies with a sample of 70 people with the sampling technique using purposive sampling. Hypothesis testing using Path Analysis and testing the mediating effect with the Sobel Test. The results of the study show that partially there is a positive and significant influence between competitiveness and marketing strategy on business productivity with a coefficient of determination of 49.9%. The results showed that partially positive and significant influence between competitiveness, marketing strategy, and business productivity on profit with a coefficient of determination of 82.4%. The Sobel test results in the moderation test I were 2.740 and p